2021
DOI: 10.1017/cts.2021.801
|View full text |Cite
|
Sign up to set email alerts
|

Excess dietary fructose does not alter gut microbiota or permeability in humans: A pilot randomized controlled study

Abstract: This version may be subject to change during the production process.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
9
2
Order By: Relevance
“…These findings are in contrast to those recently published by others, reporting that in a double-blind, cross-over design study with 10 obese subjects, the isocaloric substitution of complex carbohydrates with 75 g of either fructose or glucose for 2 weeks had no effect on fecal microbiota composition, gut permeability, or indices of endotoxemia [156]. Differences between our study [7] and that of Alemán et al [156] might have resulted from the study design (standardized nutrition vs. exchange of parts of the complex carbohydrates), the dose of fructose (25E% vs. ~20E%) but also the parameters detected (bacterial endotoxin vs. CD14, intestinal fatty acid binding protein and LPS binding protein). However, the divagating results also underlie the need for further well-designed studies.…”
Section: How Could Dietary Fructose Add To the Development Of Nafld? ...contrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are in contrast to those recently published by others, reporting that in a double-blind, cross-over design study with 10 obese subjects, the isocaloric substitution of complex carbohydrates with 75 g of either fructose or glucose for 2 weeks had no effect on fecal microbiota composition, gut permeability, or indices of endotoxemia [156]. Differences between our study [7] and that of Alemán et al [156] might have resulted from the study design (standardized nutrition vs. exchange of parts of the complex carbohydrates), the dose of fructose (25E% vs. ~20E%) but also the parameters detected (bacterial endotoxin vs. CD14, intestinal fatty acid binding protein and LPS binding protein). However, the divagating results also underlie the need for further well-designed studies.…”
Section: How Could Dietary Fructose Add To the Development Of Nafld? ...contrasting
confidence: 99%
“…Results of studies of our own group suggest that in dietetically standardized young healthy adults, consumption of a fructose-rich diet (25% of total energy intake) for only 3 days results in significantly increased plasma endotoxin concentrations while similar effects were not found when the same subjects consumed isocaloric amounts of glucose [7]. These findings are in contrast to those recently published by others, reporting that in a double-blind, cross-over design study with 10 obese subjects, the isocaloric substitution of complex carbohydrates with 75 g of either fructose or glucose for 2 weeks had no effect on fecal microbiota composition, gut permeability, or indices of endotoxemia [156]. Differences between our study [7] and that of Alemán et al [156] might have resulted from the study design (standardized nutrition vs. exchange of parts of the complex carbohydrates), the dose of fructose (25E% vs. ~20E%) but also the parameters detected (bacterial endotoxin vs. CD14, intestinal fatty acid binding protein and LPS binding protein).…”
Section: How Could Dietary Fructose Add To the Development Of Nafld? ...contrasting
confidence: 70%
“…We retrieved 4616 reports from databases and manual searches, 4433 of which were excluded based on the title or abstract. Of the 174 reports reviewed in full text, 51 reports of controlled feeding trials (75 trial comparisons, n = 2059) met the eligibility criteria [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. These trials included ten different food sources of fructos...…”
Section: Resultsmentioning
confidence: 99%
“…In view of this, a significant reduction in fructose, sucrose and HFCS in processed foods, beverages and a general ban on high-fructose corn syrup are advised [38,87,92,137,145,146,250]. The role of fructose in the intestinal microbiome and gut barrier function remains under debate [120,122].…”
Section: Discussionmentioning
confidence: 99%
“…reported that a high-fructose diet was associated with lower abundance of beneficial microbes (Eubacterium and Streptococcus), which are involved in carbohydrate metabolism, aiding dysbiosis [121]. A 2020 study by Aleman et al demonstrated that a daily dose of 75 g of fructose in obese patients did not cause increased gut permeability or endotoxemia [122]. This contradicts previous reports that stated that fructose causes bacterial overgrowth, an increase in intestinal permeability, precipitating endotoxemia and, hence, the initiation of an inflammatory cascade driving the progression of NAFLD [123,124].…”
Section: Fructose and Sucrose-fructose And Sucrose In The Epidemiolog...mentioning
confidence: 99%